Sliding surface optimization via regional pole placement for a class of nonlinear systems - Arıcan, Ahmet Çağrı; Çopur, Engin Hasan; Inalhan, Gokhan; Salamci, Metin U. (Institute of Electrical and Electronics Engineers (IEEE), 2023)
In this paper, a new approach is introduced which combines Eigenvalue Assignment, State Dependent Riccati Equation (SDRE) and Sliding Mode Control (SMC) methods for nonlinear systems. In the classical SDRE based SMC (SDRESMC) approach, a nonlinear system is frozen at each time instant to obtain a linear-like structure model that is used to design a sliding surface (SS) at each time instant. This mechanism produces a state-dependent SS to hold the states on the SS. The approach proposed here is built on this mechanism and offers a new way to design a state-dependent SS for nonlinear systems so that the pointwise eigenvalues of the closed-loop system matrix of the control-free dynamics in the regular form can be kept in a specified disk. This gives a great advantage to shape the transient response characteristics. The performance of the nonlinear controller approach proposed here is investigated in simulations.
Keywords: nonlinear systems; eigenvalue assignment; sliding mode control; sliding surface design